Putative Degradation of Non-Stored Sperm in the Female Reproductive Tract of the Dengue Vector Mosquito Aedes aegypti (2022)
ABSTRACT: n insect vectors of disease, male and female molecules that mediate reproductive processes are promising targets to suppress fertility of these populations. One process, the storage of sperm in the female reproductive tract, is essential for optimal fertility in all organisms examined to date. In the dengue vector mosquito Aedes aegypti, female sperm storage has not been fully characterized, a requirement to identify sex-specific molecules that mediate this process. Aedes aegypti males deposit the ejaculate into the bursa of the female reproductive tract, and sperm enter the spermathecae—the long-term storage sites—quickly after insemination. However, the proportion of sperm received during mating that are stored in the spermathecae is unclear, and the fate of non-stored sperm unknown. We quantified sperm storage in two Ae. aegypti strains, mated in all combinations, and in two contexts (mass mated and when mating was observed) at 1-, 3- and 5-days post-mating. Sperm quantity in the spermathecae was similar at all timepoints; most females stored ~400 sperm on average. Sperm that did not enter the spermathecae remained in the bursa, where they declined in number and became more fragile to mechanical manipulation at each timepoint. Further, sperm viability in the bursa fell from 91.6% shortly after mating to 12.2% 24 h later. One day after insemination, ~50% of sperm detected in the female reproductive tract was stored in the spermathecae. When we quantified sperm storage in females mated to males that transferred reduced ejaculate quantities (but still able to induce optimal fertility in their mates), sperm detected in the spermathecae similarly declined; females stored ~50% of the sperm received even as sperm quantities transferred at mating declined. Our results suggest that sperm storage in Ae. aegypti females is influenced by ejaculate volume, and that sperm that do not enter the spermathecae remain in the bursa, where they appear to degrade. The consistent presence of sperm in the bursa, even when males transferred low sperm quantities, suggests that the putative degradation of bursa sperm may play a role in Ae. aegypti female fertility, potentially identifying a novel process in this important vector species.